Long Time Out: Unemployment and Joblessness in Canada and the United States - Kroft, Kory; Lange, Fabian; Notowidigdo, Matthew J.; Tudball, Matthew (Journal of Labor Economics, 2019)
We compare patterns of unemployment between Canada and the United States during the Great Recession. We document a rise in long-term unemployment in Canada, similar to findings in earlier work. We consider an extended matching model using restricted-access data from the Canadian Labour Force Survey, which contains information on time since last job for both unemployed and nonparticipants. We create a new historical vacancy series for Canada based on relative employment in “recruiting industries” to construct a monthly Beveridge curve for Canada. Allowing for duration dependence in flows between unemployment and nonparticipation is crucial for explaining long-term joblessness.